2016
DOI: 10.1177/0739986316633436
|View full text |Cite
|
Sign up to set email alerts
|

Binge-Drinking Attitudes and Behaviors Among Hispanic and Non-Hispanic College Students

Abstract: This study explores binge-drinking behaviors and attitudes among Hispanic and non-Hispanic college students. The authors surveyed students at the same large Hispanic-serving university used in a 1999 study by Bennett et al., partially replicating that earlier research. While the percentage of students who reported binge drinking in the present study did not differ significantly by ethnicity, Hispanic students showed the most dramatic decrease in bingedrinking behavior since the 1990s study. Perhaps not coincid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Scientific research shows that men are more likely to drink and drink more than women [20,61,63,[71][72][73]; this prediction reaches up to 2.55 times higher [6]. In other studies, this difference is decreasing [7,74] and the present study does not find differences in risky drinking between male and female students [65].…”
Section: ■ Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Scientific research shows that men are more likely to drink and drink more than women [20,61,63,[71][72][73]; this prediction reaches up to 2.55 times higher [6]. In other studies, this difference is decreasing [7,74] and the present study does not find differences in risky drinking between male and female students [65].…”
Section: ■ Discussionsupporting
confidence: 46%
“…Another factor that seems to contribute to the increase in risky drinking in higher education students is the place of residence. This study revealed that students who lived at home with their parents consumed less alcohol than expected [42,65,72,73,81]. Parental supervision in this case seems to play an essential role in the prevention and monitoring of risky behaviours related to alcohol consumption, with a lower rate of excessive alcohol consumption and drunkenness episodes in students who did not change their residence at the time of entry into higher education.…”
Section: ■ Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The primary contribution of the present studies is the consideration of motivations for responsible drinking in college drinking interventions to promote PBS use. Thus, given the existence of health disparities regarding alcohol-related outcomes among Hispanic college students (e.g., Shields et al, 2016), we conducted exploratory analyses testing differences between Hispanic and non-Hispanic participants relating to motivations for responsible drinking. There were no differences between groups on autonomous motivation, but Hispanic participants were higher on introjected regulation and lower on external regulation and amotivation than non-Hispanic participants.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the lack of effectiveness may have been that health campaigns typically target the general population and that specific tailoring for sexual minorities is mostly done in health campaigns on issues such as safe sex. It is vital that health campaigns on binge drinking explicitly target high-risk groups (Shields et al, 2016 ) and in particular vulnerable LGBTQ + groups (Drabble & Eliason, 2021 ).…”
Section: Detrimental Health and Wellbeing Consequences Of (Measures A...mentioning
confidence: 99%